Efficient and stereoselective nitration of mono- and disubstituted olefins with AgNO2 and TEMPO - Maity, Soham; Manna, Srimanta; Rana, Sujoy; Naveen, Togati; Mallick, Arijit; Maiti, Debabrata (Journal of the American Chemical Society, 2013)
Nitroolefin is a common and versatile reagent. Its synthesis from olefin is generally limited by the formation of mixture of cis and trans compounds. Here we report that silver nitrite (AgNO2) along with TEMPO can promote the regio- and stereoselective nitration of a broad range of olefins. This work discloses a new and efficient approach wherein starting from olefin, nitroalkane radical formation and subsequent transformations lead to the desired nitroolefin in a stereoselective manner.